Knowledge and attitude on tuberculosis among college students in Cambodia - Ly, Chanvatanak; Yich, Punreay; Thon, Kanha; Pen, Narem; Thol, Sreynut; Nou, Maly; Sokhun, Chhorn (The Journal of Palembang Nursing Studies, 2023)
Background: Tuberculosis (TB) is one of the most common infectious diseases in the world, and it remains a significant public health concern. Cambodia is one of the 30 countries with the highest tuberculosis burden. Objective: to explore the knowledge and attitudes about TB and obtain sources of TB information among college students in Cambodia. Methods: The study design was descriptive and cross-sectional. The participants were 240 students from the Royal University of Phnom Penh who were chosen at random. The questionnaire was self-administered. The information was gathered in May 2019 and analyzed using descriptive and t-test statistics and the Chi-square test. To determine statistical significance, a p-value of 0.05 was used.  Results: This study revealed that students moderately understood tuberculosis (M = 27.76, range = 21 - 35). Male students had higher levels of TB knowledge than female students (X2 = 5.909, p = 0.052). Many students lacked knowledge regarding tuberculosis transmission and had a negative attitude toward tuberculosis, particularly “if they found out that they had TB” and “if they thought they had symptoms of TB.” TB data was gathered from various sources. TB knowledge was significantly related to TB information obtained by health workers (r = 0.234, p = 0.01). Conclusions: The findings emphasize increasing knowledge about tuberculosis prevention and treatment. They will be able to practice appropriate health behavior through health education effectively, and education will lead to the formation of proper attitudes about tuberculosis.